Violence and Healing: Exploring the Power of Collective Occupations - Motimele, M.R.; Ramugondo, E.L. (International Journal of Criminology and Sociology, 2014)
The effects of violence on the person are extensive, more so, for persons disabled through violence. Research in occupational therapy has shown the effectiveness of occupations in helping displaced refugees to construct new identities and navigate new ways of belonging within asylum countries. No research thus far has focussed on the role of occupation for healing in contexts of sustained violence. Aim: To explore the role of occupations in the healing journeys of people physically impaired by violence. Study Design: Qualitative; Narrative Inquiry. Methodology: Photovoice and Narrative Interviews. Data Analysis: Narrative-analytic methods were used to produce explanatory stories. Findings: These are presented with a specific focus on the impact/influence of violence on personal and societal occupational engagement and the restorative role of collective occupations within the participants’ healing journeys. The findings suggest a need to reframe violence as a collective occupation that dehumanizes, and healing as a collective process that (re)humanizes within a broader framework of Ubuntu as an interactive ethic. These findings call for a shift in focus for rehabilitation practices involving individuals disabled through violence, in contexts of sustained direct and structural violence such as South Africa.